TOWARDS A SYSTEMIC CONSTRUCTION INDUSTRY DEVELOPMENT: A RESEARCH AGENDA FOR A FRAGMENTED INDUSTRY IN AFRICA - Williams Gyadu-Asiedu (Journal of Construction Project Management and Innovation)
In spite of the several attempts by African countries to address their infrastructure needs, and despite the enormous investments injected into infrastructural development, much has not been achieved. The central problem is that researches and development issues in the industry have not taken into consideration its fragmented nature and how this impacts on the efforts being put in place. Relying on the survey of literature review, this paper proposes a research agenda for the construction industries in Africa and other developing countries in which a concerted effort based on systemic approach should be used to address the problem. It is conceived that the research and development objective of the industry in Africa could be better achieved if it is considered as a system of fragmented components. This will provide a framework in which the General Systems Theory which will enable the application of laws and theories from other disciplines in the industry’s research and hence its development. The expected results is that improvements and developments programmes shall be focused on individual component parts whose interactions, if properly managed, will result in the development of the whole. In the process better and realistic results of infrastructural developmental agenda will be achieved